Chronic Q fever in two haemodialysis patients - Vizinho,Ricardo (2012)
Q fever is a zoonotic disease caused by the highly infectious agent Coxiella burnetii which may manifest as a fairly common acute benign disease, or a much rarer and potentially lethal chronic condition. To our knowledge, chronic Q fever has previously only been described in two dialysis patients. We report a further two cases of haemodialysis patients with chronic Q fever and hypothesise as to its possible underdiagnosis in this population. Both patients had a prosthetic heart valve and although no vegetations were found by transoesophagic echocardiography, they met the Duke criteria for possible infective endocarditis. One patient, diagnosed about 11 months after the initial clinical manifestations, died, while the other, started on doxycycline and chloroquine about 3 months after the initial clinical manifestations, survived. We underline some key points that should lead to suspicion of chronic Q fever, namely the combination of a fluctuant febrile syndrome of unknown origin, anaemia and prior heart valve disease, especially in an immunocompromised patient